2023
DOI: 10.1128/mbio.03068-22
|View full text |Cite
|
Sign up to set email alerts
|

The IRE1α-XBP1 Signaling Axis Promotes Glycolytic Reprogramming in Response to Inflammatory Stimuli

Abstract: The immune system must be able to tailor its response to different types of pathogens in order to eliminate them and protect the host. When confronted with bacterial pathogens, macrophages, frontline defenders in the immune system, switch to a glycolysis-driven metabolism to carry out their antibacterial functions.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 68 publications
0
4
0
Order By: Relevance
“…It has been proposed that glutamine concentration stimulates q Gln rate and q NH4 [ 53 ], which is valid for the TAFE.X1, which expresses lower levels of h-XBP1s and at higher [Gln] also increases q Gln . Likewise, it has also been demonstrated that upregulation and induction of XBP1s downregulated the abundance of glutamine carriers (SNAT1, SNAT2, and ASCT2), limiting the glutamine influx in T-cells [ 22 , 54 ], via degradation of the carriers via ERAD [ 24 ]. This phenomenon was observed in our higher h-XBP1s overexpressor clone (TAFE.X2), which maintained basal q Gln regardless [Gln].…”
Section: Discussionmentioning
confidence: 99%
“…It has been proposed that glutamine concentration stimulates q Gln rate and q NH4 [ 53 ], which is valid for the TAFE.X1, which expresses lower levels of h-XBP1s and at higher [Gln] also increases q Gln . Likewise, it has also been demonstrated that upregulation and induction of XBP1s downregulated the abundance of glutamine carriers (SNAT1, SNAT2, and ASCT2), limiting the glutamine influx in T-cells [ 22 , 54 ], via degradation of the carriers via ERAD [ 24 ]. This phenomenon was observed in our higher h-XBP1s overexpressor clone (TAFE.X2), which maintained basal q Gln regardless [Gln].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that macrophages obtain energy through glycolysis during inflammatory activation and that the inhibition of glycolysis can inhibit inflammation [ 22 , 23 , 24 ]. Our study found that the ECAR increased, OCR decreased, and glycolysis increased during glucose metabolism when RAW264.7 cells were stimulated by LPS.…”
Section: Discussionmentioning
confidence: 99%
“…IRE1α activity is crucial for the maturation and function of highly secretory cell types, such as plasma cells 77,78 , pancreatic beta cells 79 , macrophages 6,80 , and T cells 81 . Additionally, considering the broad roles of IRE1α and XBP1S in innate immunity, including cytokine induction 6,10 , metabolic plasticity 24 , ROS production, and microbicidal activity 12,13 , proactive strategies for IRE1α activation prior to protein misfolding may be important for innate immune regulation. Further elucidation of the mechanisms driving protein misfolding-independent IRE1α activation will identify targets for tuning of IRE1α activity, with potential for therapeutic utility for diseases in which aberrant IRE1α activity may contribute to disease progression, such as cancer and obesity 82,83 .…”
Section: Discussionmentioning
confidence: 99%
“…IRE1α has broad regulatory roles and consequences for infection and immunity. For example, the IRE1α-XBP1S axis can promote the expression of proinflammatory cytokines 6,22 , modulate metabolic plasticity 24 , and promote ER homeostasis 25 during infection. Additionally, IRE1α can facilitate intra-organelle communication for ER-mitochondria calcium signaling and promotion of reactive oxygen species (ROS) generation 12,13,26 .…”
Section: Introductionmentioning
confidence: 99%